Coffee Powder Antioxidant and Acrylamide Activity in Different Processing and Roasting Methods - Analianasari, A.; Berliana, D.; Shintawati, Shintawati (Universitas Serambi Mekkah, 2021)
This research aimed to analyze the antioxidant activity of processed ground coffee and the levels of acrylamide in roasted ground coffee at different temperature levels. The research method is a descriptive qualitative method by calculating antioxidant activity with UV-Vis spectrophotometer and acrylamide content by HPLC. The results showed that the levels of acrylamide produced from processing with different roasting levels were still below the tolerance limit and had strong antioxidant activity at various roasting levels with different processing methods. Keywords: Antioxidant, acrylamide, coffee powder